Single-Use Plastic Consumption in Islamic Environmental Jurisprudence: A Maqāṣid al-Sharī'ah Analysis - Najwa Azzahra (Mir'ah: Family Law and Legal Culture, 2026)
The use of single-use plastics has become part of modern life due to their practicality and affordability. However, their excessive use has caused negative environmental impacts, such as soil, water, and marine pollution, while threatening ecosystem balance and human health. This article aims to analyze the ethics of single-use plastic consumption from the perspective of maqāṣid al-sharī'ah through the fiqh al-bi'ah approach. This qualitative research employs documentation study and descriptive-analytical analysis of relevant literature. The findings reveal that although single-use plastics offer practical benefits, their long-term negative impacts outweigh their advantages. This condition contradicts the principles of maqāṣid al-sharī'ah, particularly in protecting life (hifz al-nafs), preserving future generations (hifz al-nasl), and safeguarding wealth (hifz al-mal). From an environmental perspective, preserving nature is a moral responsibility of humans as khalifah on earth. The contribution of this article is to provide a normative ethical framework based on maqāṣid that can serve as a foundation for fatwas, policies, and ecological awareness movements among Muslims. However, this study has limitations as it has not thoroughly examined the socio-economic aspects of underprivileged communities, the availability of alternative infrastructure, and the roles of industry and government in supporting comprehensive behavioral transformation. Therefore, reducing single-use plastic consumption and shifting to environmentally friendly behavior are concrete forms of implementing Islamic values in realizing public welfare and maintaining environmental sustainability.